Avaliação da presença de microrganismos indicadores de contaminação e patogênicos em líquidos lixiviados do aterro sanitário de Belo Horizonte - Celia de Fatima Machado (2004)
This work study the presence of environmental contamination indicators and pathogenic microorganisms in the leachate of two different cells located at the sanitary landfill of Belo Horizonte, State of Minas Gerais, Brazil, as follows: Emergency Cell (disposal of solid urban waste; closed in August, 1997) and AC05 Cell (co-disposal of solid urban and hospital waste; operating during the samples collection). From January until April, 2003, 25 samples of leachate were collected at the studied cells.The following physical and chemical parameters were analysed: pH, Temperature, Potential Redox and Conductivity as well as the microbial parameters: total and thermotolerant coliforms, Enterococcus, Clostridium perfringens (contamination indicators) besides theaerobic bacterias and the microorganisms commonly related to the hospital infection as Pseudomonas aeruginosa and Staphylococus aureus. The leachate of the ACO5 cell, presented greater value for conductivity and temperature and lower value for redox potential. The pH values of ACO5 and emergencial cells were close. Except for the Staphylococus aureus, all others microorganisms studied were detected in both cells. The concentrations of the contamination indicators: total coliforms, thermotolerant coliforms and Clostridium perfringens was greater in ACO5 cell. On the other hand, statistics difference between the Enterococcus group and the aerobics bacteria Pseudomonasaeruginosa were not observed. Regarding to the susceptible to antimicrobials, the Pseudomonas aeruginosa strains that wasisolated of the leachate of the ACO5 cell, had shown greater resistance rate (20,69%) to tested antibiotics than emergencial cell ( 7,6%). The strains of the both cells had shown multiple resistance to the antibiotics commonly used in the human infections and only in the AC05 cells was detected resistance to imipenem, carbapenêmico (4th generation) andtreatment more efficient of caused infections to Pseudomonas aeruginosa. The results of this research alert for the possibility of the presence of other pathogenic microorganisms of the RSU and RSS and indicates that so far the leachate of the ACO5 cell, from co-disposal of solid urban and hospital waste as well as the leachate of the emergencial cell, from mono disposal of solid urban waste, can represent biological risks to the public health and environment.